Efficacy and tolerability of tirzepatide, a dual glucose‐dependent insulinotropic peptide and glucagon‐like peptide‐1 receptor agonist in patients with type 2 diabetes: A 12‐week, randomized, double‐blind, placebo‐controlled study to evaluate different dose‐escalation regimens. Issue 6 (11th February 2020) - Frias, Juan Pablo; Nauck, Michael A.; Van, Joanna; Benson, Charles; Bray, Ross; Cui, Xuewei; Milicevic, Zvonko; Urva, Shweta; Haupt, Axel; Robins, Deborah A.
Abstract: Aim: To assess the efficacy and tolerability of tirzepatide treatment using three different dose‐escalation regimens in patients with type 2 diabetes. Materials and Methods: In this double‐blind, placebo‐controlled study, patients were randomized (1:1:1:1) to receive either once‐weekly subcutaneous tirzepatide or placebo. The tirzepatide dose groups and dose‐escalation regimens were: 12 mg (4 mg weeks 0–3; 8 mg weeks 4–7; 12 mg weeks 8–11), 15 mg‐1 (2.5 mg weeks 0–1; 5 mg weeks 2–3; 10 mg weeks 4–7; 15 mg weeks 8–11) and 15 mg‐2 (2.5 mg weeks 0–3; 7.5 mg weeks 4–7; 15 mg weeks 8–11). The primary objective was to compare tirzepatide with placebo in HbA1c change from baseline at 12 weeks. Results: Overall, 111 patients were randomized: placebo, 26; tirzepatide 12 mg, 29; tirzepatide 15 mg‐1, 28; tirzepatide 15 mg‐2, 28. The mean age was 57.4 years, HbA1c 8.4% and body mass index 31.9 kg/m 2 . At week 12, absolute HbA1c change from baseline (SE) was greater in the tirzepatide treatment groups compared with placebo (placebo, +0.2% [0.21]; 12 mg, −1.7% [0.19]; 15 mg‐1, −2.0% [0.20]; 15 mg‐2, −1.8% [0.19]). The incidence of nausea was: placebo, 7.7%; 12 mg group, 24.1%; 15 mg‐1 group, 39.3%; 15 mg‐2 group, 35.7%. Three patients discontinued the treatment because of adverse events, one from each of the placebo, 12 mg and 15 mg‐1 groups. Conclusions: Tirzepatide treatment for 12 weeks resulted in clinically significant reductions in HbA1c. This suggests that lower starting doses and smaller dose increments are associated with a more favourable side effect profile.